2013
DOI: 10.1007/s12263-013-0350-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic modulation of the serotonergic pathway: influence on weight reduction and weight maintenance

Abstract: The serotonergic pathway plays a major role in the development of obesity. Its activity can be modulated by the 5-HT transporter-linked polymorphic region in the SLC6A4 gene and the upstream variable number of tandem repeats polymorphism in the MAOA gene. We studied whether these genetic modulations have an influence on weight reduction and weight maintenance in a one-year weight reduction program (OPTIFAST Ò 52). The polymorphisms were genotyped by PCR in a sample of 135 female and 67 male subjects with sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Both 5-HTTLPR and MAOA polymorphisms have also been associated with depression in previous studies (Caspi et al, 2003;Bonvicini et al, 2010), and it has been shown that depression is a likely contributor to obesity, particularly in women (Scott et al 2008;Anderson et al 2007). Thus, modulation of the serotonergic pathway by either 5-HTTLPR or MAOA polymorphisms could lead to elevated depression symptoms and ultimately to a reduced weight loss and/or maintenance (Wallmeier et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both 5-HTTLPR and MAOA polymorphisms have also been associated with depression in previous studies (Caspi et al, 2003;Bonvicini et al, 2010), and it has been shown that depression is a likely contributor to obesity, particularly in women (Scott et al 2008;Anderson et al 2007). Thus, modulation of the serotonergic pathway by either 5-HTTLPR or MAOA polymorphisms could lead to elevated depression symptoms and ultimately to a reduced weight loss and/or maintenance (Wallmeier et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that genetic modulation of the serotonergic pathway by polymorphic regions in the serotonin transporter gene (5-HTT; Gene Symbol: SLC6A4; chr: 17q11.2) and in the monoamine oxidase A (MAOA; chr: Xp11.3) gene may play a role in the development of obesity, although results are still controversial (Ducci et al, 2006;Fuemmeler et al, 2008;Sookoian et al, 2007Sookoian et al, , 2008Peralta et al, 2012;Wallmeier et al, 2013). The serotonin transporter 5-HTT is a key molecule in the regulation of serotonin (5-HT) levels via transport of serotonin molecules from the synaptic cleft into presynaptic neurons (Blakely et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…This study involved 29 subjects (18 women and 11 men) randomly and retrospectively selected from the OPTIFAST®52 program (franchise holder Nestlé Inc., Switzerland) at the University Hospital of Heidelberg. The OPTIFAST®52 program is a 52-week lifestyle intervention that has been previously described [ 10 ]. For the purpose of this study, patient samples and data were studied at three time-points: at the beginning of the program (T0), after 12-week of active weight loss phase through a low-calorie formula-diet (T1) and after 40-week of weight maintenance phase (T2).…”
Section: Methodsmentioning
confidence: 99%
“…The primary role of MAOA in regulating catecholamine turnover and hence ultimately influencing their levels indicates that its VNTR is a highly plausible candidate for affecting individual differences in physiological and psychological traits, such as obesity, personality traits, and alcoholism risk [150]. A previous study showed a significant association of MAOA VNTR alleles (either alone or with combination of other gene variants) with weight and BMI in Caucasian populations [98, 151153], while our unpublished study showed association only with weight; both studies agree that subjects having the lower activity 3R allele tend to have a lower weight than the higher activity 4R allele. Meanwhile, another study showed a significant association of this VNTR with obesity in a mixed-ethnic American population [154], while Dias et al [116] and our unpublished studies showed otherwise.…”
Section: Main Textmentioning
confidence: 99%